Application of Digital Literacy Media in Improving the Reading Habits of Students in Class IV SD Negeri 25 - Nurfia Abdullah; Iwan Irawan; Wiwin R Redjeb (Edumaspul: Jurnal Pendidikan, 2025)
The issue raised in this study is how to apply digital literacy media to improve the reading habits of fourth-grade students at SD Negeri 25 in Mandioli Selatan District, South Halmahera Regency. This study aims to enhance the reading habits of students using digital literacy media. This Classroom Action Research (CAR) aims to improve the reading habits of fourth-grade students at SD Negeri 25, Mandioli Selatan District, South Halmahera Regency. The study subjects consisted of 24 students. The research procedure consists of four stages in each cycle: planning, action implementation, observation, and reflection. The indicators of achievement in this study are the attainment of complete reading habits. Data collection was carried out using techniques such as observation, tests, interviews, and documentation. The results of the study show that the achievement of student activity can be seen from the results: 37.5% in cycle I, and an increase to 72.7% in cycle II. This increase can be seen from the students' learning outcomes in each cycle, which suggests that there was an improvement in the average score from cycle I to cycle II, and cycle III is no longer necessary, resulting in an improvement in reading ability.